Classification of Biophilic Buildings as Sustainable Environments - Indre Grazuleviciute-Vileniske; Aurelija Daugelaite; Gediminas Viliunas (Buildings, 2022)
Biophilic design approach aims at creating favorable conditions for humans in various types of anthropogenic environments, while at the same time restoring broken human–nature connection. The biophilic design guidelines and principles are general and flexible and allow wide array of architectural expressions. In order to better understand the architectural expression possibilities provided by biophilic design approach, the existing classifications of biophilic architecture and biophilic design examples were analyzed with the aim to develop the classification that would reflect the links between a building’s architectural expression and biophilic qualities. Three categories of biophilic architecture were distinguished in the developed classification: mimetic, applied, and organic. The distinguished categories were illustrated with the characteristic building examples and the evaluation of biophilic qualities and human-nature collaboration potential of these example buildings was carried out using comprehensive system of criteria. The analysis has demonstrated that all three distinguished categories—mimetic, applied, organic—allow for the creation of biophilic environments and hold the potential for human–nature collaboration, although organic biophilic design would be currently considered as the least developed, although most promising category.